Do Cardiac Rehabilitation Programs Offer Cardiopulmonary Resuscitation Training in Australia and New Zealand? - Cartledge, S.; Bray, Janet; Stub, D.; Krum, H.; Finn, J. (2015)
© 2016 Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) and the Cardiac Society of Australia and New Zealand (CSANZ). Background: Cardiac rehabilitation may provide an ideal environment to train high-risk cardiac patients and their families in cardiopulmonary resuscitation (CPR). However, whether this training is currently offered is unknown. The aims of this study were to: 1) describe the prevalence of CPR training in cardiac rehabilitation programs in Australia and New Zealand (NZ); and 2) examine perceived barriers and attitudes of cardiac rehabilitation coordinators towards providing CPR training. Methods: We conducted a cross-sectional online survey of Australian and NZ cardiac rehabilitation coordinators. Results: We received 253 completed surveys (46.7% response rate) (Australia n=208, NZ n=45). Cardiopulmonary resuscitation training was included in 23.9% of Australian programs and 56.6% in NZ. Common barriers to CPR training included lack of resources (49.7%) and a lack of awareness to provide CPR training for this high-risk group (33.7%). The majority of coordinators believed that lay people should be trained in CPR (96.3%) and were comfortable with recommending CPR training to this high-risk group (89.4%). Conclusions: While cardiac rehabilitation coordinators have positive attitudes towards CPR training, it is not currently part of most programs - particularly in Australia. Organisations formulating cardiac rehabilitation recommendations and guidelines should give consideration to include the provision of CPR training.